2013
DOI: 10.1021/pr4002178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amphotericin B on the Metabolic Profiles of Candida albicans

Abstract: Amphotericin B (AmB) is a polyene antifungal drug widely used for systemic fungal infections. In this study, a metabonomic method using gas chromatography-mass spectrometry (GC/MS) was developed to characterize the metabolic profiles of Candida albicans cells exposed to AmB. Thirty-one differentially produced metabolites between AmB-treated and the control groups were identified, among which 10 metabolites were upregulated and 21 metabolites were downregulated. These differentially produced metabolites were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 69 publications
(94 reference statements)
0
15
0
Order By: Relevance
“…Twenty-milliliter working cultures were prepared by diluting the preculture to an OD 620 of 0.1 with YNB medium supplemented with 1.5 mg/liter AA or the respective amount of solvent (methanol) for 4 h. Six biological replicates were used for the treated group and the control group. The extraction of intracellular metabolites was done as described in literature (34,35). Briefly: the cell pellet was obtained by 5 min of centrifugation (10,000 ϫ g, 4°C), fixed with 60% cold MeOH in NaCl buffer, and washed with 5 ml cold phosphate-buffered saline (PBS) 3 times.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-milliliter working cultures were prepared by diluting the preculture to an OD 620 of 0.1 with YNB medium supplemented with 1.5 mg/liter AA or the respective amount of solvent (methanol) for 4 h. Six biological replicates were used for the treated group and the control group. The extraction of intracellular metabolites was done as described in literature (34,35). Briefly: the cell pellet was obtained by 5 min of centrifugation (10,000 ϫ g, 4°C), fixed with 60% cold MeOH in NaCl buffer, and washed with 5 ml cold phosphate-buffered saline (PBS) 3 times.…”
Section: Methodsmentioning
confidence: 99%
“…clinical isolates (including C. albicans, C. parapsilosis and C. krusei) were obtained from Shanghai Changhai Hospital and Skin Disease Hospital (Shanghai, China). The SPE1 null mutant (spe1Δ/Δ) and reintroduced strains were constructed in our previous study [15]. Stock cultures of the strains were routinely maintained on Sabouraud dextrose agar (4% w/v dextrose, 1% w/v peptone and 1.8% w/v agar) and grown in YPD liquid medium (1% yeast extract, 2% peptone, and 2% dextrose) with constant shaking at 30°C.…”
Section: Strains Cultures and Chemicalsmentioning
confidence: 99%
“…Recently, metabolomics has been widely applied to study the mechanisms by which different agents exert their antimicrobial effects against fungi and bacteria. For example, the activity of amphotericin B against C. albicans can be attributed to changes in metabolite production (Cao et al, 2013). Another study found that the microbiostatic effect of ε-Poly-L-lysine on Saccharomyces cerevisiae is achieved by breaking the balance of intracellular metabolites due to disruptions in cell membrane function (Bo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%